The efficient use of different fungal bioagents for eco-friendly management of fusarium wilt disease of tomato - Gavilán Figari, Isabel Milagros (2022)
Tomato (Lycopersicon esculentum L.) is one of the most important vegetables, used as condiments, salad and cooked with various recipes. It is a good source of vitamin C, A, calcium, iron etc. However, per acre yield in Pakistan is quite lower as compared to other countries of the world due to various factors, including diseases. Tomato crop suffers by approximately 200 diseases worldwide, among them, Fusarium wilt of tomato is highly destructive fungal disease and has caused losses up to 49.5% in Pakistan. Early strategies to manage this devastating disease include the use of cultural, physical, and chemical control are suggested, but none of these provided positive impact except cultural methods. Keeping in view the importance and losses caused by Fusarium wilt of tomato the studies on its management with fungal bioagents was conducted. For this. different bioagents were tested in lab and fields against Fusarium oxysporum f.sp. lycopersici. The highest inhibition 89.63% was noted by Trichoderma harzianum followed by Neurospora sp. 87.40% in the poisoned food method. In pot experiments, the T. harzianum was found as highly successful then Neurospora sp., Chaetomium subaffine and Arthrinium sp. providing minimum disease incidence and lowest mortality percent at higher and medium concentrations. The highest plant biomass and lowest root infection percent were noted in T. harzianum followed by Neurospora sp., C. subaffine and Arthrinium sp. at medium and lower doses. The lowest response was recorded by Nigrospora sphaerica and Dermateaceae sp. In in-vivo trials, the highest response was observed in the treatment of T. harzianum followed by Neurospora sp., Arthrinium sp., N. sphaerica, respectively. The highest fruit yield was recorded by T. harzianum 6.66 (kg) and Neurospora sp. 5.66 (kg). Interestingly, Neurospora sp., Arthrinium sp., N. sphaerica, and Dermateaceae sp. have been first time recognized in the current study as potential bioagents against fusarium wilt of tomato. Based on the findings, it is suggested that T. harzianum and Neurospora sp., may be used as potential bioagents for ecofriendly management of tomato wilt disease.